Development of P5 Module Based nn Experiential Learning “Recycling Plastic Waste” on the Theme of Sustainable Lifestyle of Elementary School Students - Ningsih, Umi; Arafat, Yasir; Faipri Selegi, Susanti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This research and development aims to develop a P5 Module Based on Experential Learning "Recycling of Plastic Waste" on the Theme of Sustainable Lifestyle for Elementary School Students which is very valid and practical. The type of research used is Research and Development (RnD) with the ADDIE (Anlyze, Design, Development, Implementation, and Evaluation) development model. The data collection techniques in this study are in the form of questionnaires and documentation. This research uses validity and practicality analysis techniques. The results of the three validators got the following percentages: linguists got a percentage of 85%, material experts got a percentage of 82%, and media experts got a percentage of 83%, by meeting the "very valid" criteria. The P5 module was also declared practical which can be proven through interviews with class teachers about the P5 module and proven through a one-to-one trial conducted by 3 students who obtained an average percentage of 82.67%. with the criterion of "very practical", and the small group trial was carried out by 8 students with an average percentage of 85% with the criterion of "very practical". It can be concluded that the Experiential Learning-Based P5 Module is very valid and practical to be used as a teaching material in the P5 learning "Plastic Waste Cycle" on the Theme of Sustainable Lifestyle for Grade V Students of SD Negeri 4 Rimau Island for the 2025/2026 academic year.